Tiga Elemen Penting dalam Produksi Iklan Digital Item Virtual Mobile Legends - Ernanda, Andrya Raffy; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Digital games have transformed into immersive marketing platforms through strategic in-game advertising. Mobile Legends: Bang Bang is among Indonesia’s most widely played online games, offering purchasable virtual items like skins and battle passes. These are promoted through visually engaging and emotionally persuasive advertising. This study investigates the influence of advertising appeal on players’ purchase intention among EZPZ Coffee visitors. Grounded in the AIDA theory, this research explores advertising appeal through the dimensions of trustworthiness, attractiveness, and informativeness, while purchase intention is measured using transactional, referential, preferential, and exploratory dimensions. A quantitative approach was employed using a survey method and purposive sampling technique. Data was collected through a survey distributes to 100 respondents, each of whom active Mobile Legends players and regular EZPZ Coffee customers. The data were analyzed using SPSS with multiple linear regression. The results demonstrate that advertising appeal significantly affects purchase intention, with trustworthiness and attractiveness being the dominant factors. The coefficient of determination is 74.9%, indicating that advertising appeal strongly influences players’ purchase decisions, while 25.1% is explained by other variables. These findings highlight the importance of creating credible, visually compelling advertisements to increase virtual item sales in online gaming environments. Permainan digital telah bertransformasi menjadi platform pemasaran yang imersif melalui strategi iklan dalam game yang semakin canggih. Mobile Legends: Bang Bang menjadi salah satu game online terpopuler di Indonesia yang menawarkan item virtual seperti skin dan battle pass yang dipromosikan melalui iklan menarik dan persuasif. Penelitian ini bertujuan untuk menganalisis pengaruh daya tarik iklan terhadap minat beli pemain dari pengunjung EZPZ Coffee. Penelitian ini berlandaskan teori AIDA dan mengukur daya tarik iklan melalui dimensi trustworthiness, attractiveness, dan informativeness, sedangkan minat beli diukur melalui dimensi transaksional, referensial, preferensial, dan eksploratif. Pendekatan kuantitatif digunakan dengan metode survei dan teknik purposive sampling. Data dikumpulkan melalui kuesioner kepada 100 responden yang merupakan pemain aktif Mobile Legends dan pengunjung EZPZ Coffee. Analisis dilakukan menggunakan regresi linier bergaanda dan SPSS. Temuan menunjukkan bahwa daya Tarik iklan berdampak besar pada minat beli, terutama pada dimensi trustworthiness dan attractiveness. Koefisien determinasi sebesar 74,9% menunjukkan bahwa daya tarik iklan sangat memengaruhi minat beli pemain, sementara 25,1% dipengaruhi oleh variabel lain. Temuan ini menegaskan pentingnya merancang iklan yang kredibel dan menarik untuk meningkatkan penjualan item virtual dalam game.